Tuberculosis Infection Status Post Partial Knee Arthroplasty: A Novel Treatment Approach. Issue 6 (November 2016) - Brown, Sheldon; Berger, Ryan; Ramgopal, Moti; Dahya, Vishal
Abstract : Abstract: A 55-year-old hospitalized woman presented with a right knee wound and associated swelling, hemarthrosis, and persistent pain 2 weeks after undergoing a right knee hemiarthroplasty. The right knee wound was cultured and results revealed Mycobacterium tuberculosis . Right knee hardware was removed; irrigation and debridement were performed. An antibiotic spacer impregnated with isoniazid was then inserted into the wound cavity. The patient successfully completed a 6-month regimen of antituberculosis medication therapy, and subsequent knee cultures were negative. A total knee arthroplasty revision was performed following eradication of tuberculosis and the patient remained symptom free with a fully functional total knee arthroplasty.